2012
DOI: 10.1144/sp364.14
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the influence of solution-enhanced conduits on catchment-scale contaminant transport in the Hertfordshire Chalk aquifer

Abstract: Catchment-scale (>40 km2) contamination of the Chalk aquifer of Hertfordshire by bromate, emanating from a disused industrial site north of St Albans, represents the largest occurrence of point-source groundwater contamination in the UK. The influences of ‘double porosity’ diffusive exchange and rapid transport along solution-enhanced conduits complicate predictive modelling of contaminant transport to threatened public supply wells. Tracer testing indicates that solution-enhanced flow routes exist beyond t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…In the Lee Valley north-east of London, source protection zones for three public-supply wells gave 50-day time-of-travel zones that extended about 1 km upgradient from the wells. However, tracer studies showed that the travel time for a distance of 16 km to the wells was a mere four days, demonstrating that the modeled source protection zones were far too small (Cook et al, 2012;Worthington, 2015).…”
Section: Cretaceous Limestone (Chalk) In Hertfordshire Ukmentioning
confidence: 96%
See 2 more Smart Citations
“…In the Lee Valley north-east of London, source protection zones for three public-supply wells gave 50-day time-of-travel zones that extended about 1 km upgradient from the wells. However, tracer studies showed that the travel time for a distance of 16 km to the wells was a mere four days, demonstrating that the modeled source protection zones were far too small (Cook et al, 2012;Worthington, 2015).…”
Section: Cretaceous Limestone (Chalk) In Hertfordshire Ukmentioning
confidence: 96%
“…Total porosity in the aquifer is 38%, but travel times of artificial tracers from sinking streams and of a long-persistence bromate plume were matched using MODFLOW and MT3DMS by using an effective porosity of 0.01% along flowpaths from sinking streams, and an effective porosity of 1-5% in the remainder of the model (Cook et al, 2012). A second model used a dual-continuum approach, with an effective porosity of 2% to match seasonal variation in water levels in one continuum, and an effective porosity of 5-10% in the second continuum to match drainage of the matrix over multi-year droughts (Taylor et al, 2012).…”
Section: Cretaceous Limestone (Chalk) In Hertfordshire Ukmentioning
confidence: 99%
See 1 more Smart Citation
“…Two of these papers consider major pollution incidents on the Chalk aquifer and the simulation of contaminant transport at a regional scale (Cook et al 2012;Watson et al 2012). These papers form a useful contrast with the papers written by the practitioners, as they give some insight into the ways in which the regional models of the Environment Agency can be used, improved and/or adapted to assess future trends in water quality.…”
Section: Research and Futurementioning
confidence: 99%
“…These papers form a useful contrast with the papers written by the practitioners, as they give some insight into the ways in which the regional models of the Environment Agency can be used, improved and/or adapted to assess future trends in water quality. In the case of Cook et al (2012), the contaminant transport model has been partly based on the Environment Agency regional groundwater model. Some of the academic papers also provide an insight into the information exchange between practitioners and academics.…”
Section: Research and Futurementioning
confidence: 99%